2017
DOI: 10.1177/0894318417741119
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Korean Nurses During the Middle East Respiratory Syndrome Outbreak

Abstract: The authors in this article explore the experiences of eight South Korean nurses during an outbreak of the Middle East Respiratory Syndrome (MERS), which took place in the fall of 2015. These nurses were mandated to remain in isolation in an intensive care unit (ICU) dedicated to the treatment of the patients with the MERS virus for 7 days. Parse's humanbecoming theory was used to frame the discussion. Three themes found in the nurse's stories are discussed: feeling hopeless and cut off, feeling shame and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(95 citation statements)
references
References 3 publications
(6 reference statements)
2
91
0
2
Order By: Relevance
“…Nurses experienced difficulty with nursing work due to the loss of proprioception associated with thick gloves and heavy protective equipment. Nurses also experienced physical symptoms, such as dyspnoea, headache, blurred vision, nausea and vomiting, when wearing personal protective equipment for the first time, as in previous studies (Im et al, 2018;Kim, 2018;Liu & Liehr, 2009;Park et al, 2018). The nurses said that the harsh environment of the temporary negative-pressure isolation room was like a "field hospital" on the battlefield, and expressed that they felt their life was threatened when they were exposed to a confirmed MERS case in an "instantaneous situation."…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Nurses experienced difficulty with nursing work due to the loss of proprioception associated with thick gloves and heavy protective equipment. Nurses also experienced physical symptoms, such as dyspnoea, headache, blurred vision, nausea and vomiting, when wearing personal protective equipment for the first time, as in previous studies (Im et al, 2018;Kim, 2018;Liu & Liehr, 2009;Park et al, 2018). The nurses said that the harsh environment of the temporary negative-pressure isolation room was like a "field hospital" on the battlefield, and expressed that they felt their life was threatened when they were exposed to a confirmed MERS case in an "instantaneous situation."…”
Section: Discussionmentioning
confidence: 73%
“…Many study showed that nurses felt uncertainty due to fear of MERS, the lack of a treatment policy, the ever-changing guidelines, confusion about how to control the infection and the lack of education about new diseases (Chung, Wong, Suen, & Chung, 2005;Im et al, 2018;Kim, 2018;Park et al, 2018). This increased anxiety and fear in nurses, who need to take care of patients with new infectious diseases (Abolfotouh et al, 2017;Alsubaie et al, 2019;Kim, 2018); the fears of our participants were of a similar nature.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The experiences of nurses who cared for MERS-CoV patients in Korea were also studied by other researchers. Im et al 25 interviewed 8 intensive care unit nurses who cared for MERS-CoV patients in Korea and identified 3 relevant factors: "feeling hopeless and cut off," "feeling shame and overworked," and "feeling the pride of fulfilling a duty." In addition, when compared to the experiences of nurses who cared for SARS, H1N1, and ebola patients, the experiences of patient care for emerging infectious diseases were similar in terms of nurses' physical and emotional exhaustion, frustration, and fulfillment.…”
Section: Discussionmentioning
confidence: 99%